2014
DOI: 10.1128/aac.02045-13
|View full text |Cite
|
Sign up to set email alerts
|

Role of the mecA Gene in Oxacillin Resistance in a Staphylococcus aureus Clinical Strain with a pvl -Positive ST59 Genetic Background

Abstract: The most prevalent community-associated methicillin-resistant Staphylococcus aureus (C-MRSA) strains in Taiwan, sequence type 59 (ST59) clones, carry staphylococcal cassette chromosome mec (SCCmec) type V and, to a lesser extent, type IV. These strains show wide variation in sensitivity to oxacillin, but the reasons for this variation are unknown. Here we compared the sequences of the mecA genes from clinical strains of different SCCmec types and found that they contain different mecA promoter mutations. Analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 40 publications
3
24
1
Order By: Relevance
“…The first mutation was a G to T transversion in the mecA ribosomal binding site (RBS), seven nucleotides upstream of mecA start codon (Fig 3a). Isolates with the mecA [-7]:T allele had a median penicillin-clavulanic acid MIC of 0.125 μg/ml (range <0.016 -6) compared to a median of 8 μg/ml (range: 0.023 -96) for isolates with the 'wildtype' mecA [-7]:G. Previous work has demonstrated that despite being in the RBS, the T allele results in lower mecA transcript and PBP2a expression levels 28 .…”
Section: A Combination Of Meca Promoter Mutations and Pbp2a Substitutmentioning
confidence: 99%
“…The first mutation was a G to T transversion in the mecA ribosomal binding site (RBS), seven nucleotides upstream of mecA start codon (Fig 3a). Isolates with the mecA [-7]:T allele had a median penicillin-clavulanic acid MIC of 0.125 μg/ml (range <0.016 -6) compared to a median of 8 μg/ml (range: 0.023 -96) for isolates with the 'wildtype' mecA [-7]:G. Previous work has demonstrated that despite being in the RBS, the T allele results in lower mecA transcript and PBP2a expression levels 28 .…”
Section: A Combination Of Meca Promoter Mutations and Pbp2a Substitutmentioning
confidence: 99%
“…PBP2a, encoded by mecA, is an alternative cell wall cross-linking enzyme with reduced affinity for virtually all β-lactam antibiotics. Previous studies showed that the expression of mecA closely correlated with the level of oxacillin resistance [5]. mecA is part of the staphylococcal chromosome cassette (SCCmec), which is present in MRSA but absent in methicillin (oxacillin)-susceptible S. aureus (MSSA) [6].…”
mentioning
confidence: 99%
“…Furthermore, excision of the SCCmec element in MRSA strains results in oxacillin susceptibility [8]. Likewise, inactivation of mecA in MRSA strains reverses the MRSA phenotype to that of MSSA [5].…”
mentioning
confidence: 99%
“…It is plausible that these observable variations in the oxacillin MIC's may have been due to mecA promoter mutations, which play an important role in determining the level of oxacillin resistance. For example, a study done by Chen et al [25] found that the mecA promoter mutation G-25A is associated with a high oxacillin MIC (256 μg/ml); G-7T conferred a moderate oxacillin MIC (32 to 64 μg/ml); and strains with the C-33T mutation showed a low oxacillin MIC (4 to 8 μg/ml).…”
Section: Discussionmentioning
confidence: 99%